The emergence of sustainability science in the editorials of three scholarly journals - Marco Schirone (Discover Sustainability)
Abstract This study examines editorials from leading journals in sustainability science published between 1993 and 2022. By analyzing 76 editorials from Environment, Development, and Sustainability; International Journal of Sustainable Development & World Ecology; and Sustainable Development, the article investigates the field’s historical development, interdisciplinary connections, and interactions with sustainable development policies. Using qualitative content analysis, the editorials are categorized into three distinct periods: foundation (1993–2002), introspection (2003–2012), and diversification (2013–2022). The foundational phase emphasizes key themes, such as systems thinking, participatory research, and indigenous knowledge, along with the interplay between scientific knowledge and environmental policy. The introspection phase is characterized by increasing interdisciplinarity and a problem-oriented approach, focusing on socioecological and economic systems, particularly ecological modernization. The diversification period—marked by global crises like climate change and COVID-19—highlights the importance of transdisciplinarity, with a focus on involving non-academic stakeholders, including policymakers and local communities. Additionally, editorials underscore the need to address global equity while integrating cultural sustainability into sustainability efforts. The study further analyzes the diversity of research contributing to the field, key concepts, the tension between global and local perspectives, and the role of journals as gatekeepers that help establish sustainability science as an autonomous research field. Drawing on Pierre Bourdieu’s sociology of science, the article interprets sustainability science as a heterodox science that challenges the boundaries of traditional disciplines; and as a field that competes for legitimacy and recognition, balancing interdisciplinary and transdisciplinarity with its disciplinary identity.